Religious education : perspectives, teaching strategies and challenges - Coudert, Richard (Nova Science Publishers, 2019)
"Religious Education: Perspectives, Teaching Strategies and Challenges attempts to conceptualize the depth and complexity of religious education through Michael Polanyi's notions of personal knowledge and the tacit dimension of knowledge. In Israel, some non-religious Jewish families enroll their children in kindergartens of the state religious education system, even though they do not belong to the mainstream religious community. The authors offer an ethnographic study of the sociological-educational processes taking place in these kindergartens. The closing chapter discusses the possibilities for learning from Christian spirituality in the framework of a post-modern European university"-- Provided by publisher.
Keywords: Polanyi, Michael, -- 1891-1976.; Polanyi, Michael, -- 1891-1976; Religious education -- Abstracts.; Moral education -- Research -- 21st century.; Éducation religieuse -- Résumés analytiques.; Éducation morale -- Recherche -- 21e siècle.; Moral education -- Research; Religious education; 2000-2099; Abstracts